Individual Characteristics of work council members: Empirical evidence - Susi Störmer (Management Revue, 2010)
The main body of research on work councils has been conducted on a collective institutional level, neglecting work council members at an individual level. In times of changing industrial relations, the importance of work councils in management decision making has risen steadily and thus further research of its members is required. This paper sheds light onto work councillors as individuals by investigating personality and attitudinal characteristics using data from a large representative German dataset. The findings are gender-specific and suggest that female work councillors are more extraverted and exhibit a stronger internal Locus of Control, while male work councillors are more conscientious as compared to their non-councillor counterparts. Risk attitudes and reciprocity do not show as valid predictors of work council membership. Implications of the results are discussed.
Keywords: 650; work councils; Five Factor Model; risk aversion; locus of control; reciprocity